2001
DOI: 10.1128/jb.183.14.4210-4216.2001
|View full text |Cite
|
Sign up to set email alerts
|

Indole Can Act as an Extracellular Signal in Escherichia coli

Abstract: Previous work has shown that lacZ fusions to the cysK, astD, tnaB, and gabT genes in Escherichia coli are activated by self-produced extracellular signals. Using a combination of ethyl acetate extraction, reversedphase C 18 chromatography, and thin-layer chromatography, we have purified an extracellular activating signal from E. coli supernatants. Mass spectrometry revealed a molecule with an m/z peak of 117, consistent with indole. Nuclear magnetic resonance analysis of the purified E. coli factor and synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
242
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(255 citation statements)
references
References 43 publications
11
242
1
1
Order By: Relevance
“…Thus, the induction of E. coli drug exporter genes by indole is not likely to be a result of the envelope stress response. Recently, it was reported that indole acts as an extracellular signal like N-acyl homoserine lactone and AI-2 (Baca- DeLancey et al, 1999;Fuqua et al, 2001;Wang et al, 2001;Bassler, 2002;Chen et al, 2002). The indole concentration increases with cell growth as a byproduct of pyruvate production in E. coli cells (Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the induction of E. coli drug exporter genes by indole is not likely to be a result of the envelope stress response. Recently, it was reported that indole acts as an extracellular signal like N-acyl homoserine lactone and AI-2 (Baca- DeLancey et al, 1999;Fuqua et al, 2001;Wang et al, 2001;Bassler, 2002;Chen et al, 2002). The indole concentration increases with cell growth as a byproduct of pyruvate production in E. coli cells (Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The © 2004Blackwell Publishing Ltd, Molecular Microbiology , 55 , 1113-1126 indole concentration in the culture medium increases with cell growth. Wang et al . reported that indole regulates the expression of some genes such as astD , tnaB and gabT (Wang et al ., 2001). DeMoss reported that several Gramnegative species, including E. coli , Klebsiella oxytoca , Haemophilus influenzae and so on, showed indole production (DeMoss and Moser, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, E. coli may have evolved to utilize alternative signals, such as the accumulation of certain metabolites. Signaling via metabolites may allow cells to fine-tune the regulation of target genes in response to changing environmental conditions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some factors, such as indole, sodium tungstate, or zinc (27)(28)(29), induce BaeSR response and should cause interference with the acquisition of Stx phages by their potential host strains. For instance, zinc has been reported to inhibit virulence traits in pathogenic E. coli and, in particular, Stx phage induction (30).…”
Section: Discussionmentioning
confidence: 99%